Synthetic methods of pyrrolidines from N-hydroxylsulfonamides by using bis[copper(I) trifluoromethanesulfonate]-benzene complex as a redox catalyst - Liu, Zhenhong (2013)
The synthesis of azaheterocycles which are an important class of natural products and pharmacologically active compounds has been investigated for a long time and many methodologies were reported. Radical reactions were also applied to the synthesis of azaheterocycles but not very widely. In this thesis, the author describes the development of catalytic methods to synthesize 2,5-disubstituted pyrrolidines from N-alkenyl, alkynyl and alkyl N-benzoyloxysulfonamides by using (CuOTf)2•C6H6 as a redox catalyst. These reactions involve sulfonamidyl radicals as the key intermediates, which are generated by one electron reduction of N-benzoyloxysulfonamides. Thus generated sulfonamidyl radicals successively follow the two kinds of steps; 1) addition to intramolecular unsaturated bond or 2) 1,5- hydrogen abstraction. Firstly, addition of sulfonamidyl radicals to intramolecular unsaturated bond was studied, and after the screening of redox catalysts, (CuOTf)2•C6H6 was found to act as an efficient catalyst as shown in eq 1 and 2. From N-4-alkenyl-N-benzoyloxysulfonamides 1, 2,5-disubstuted pyrrolidines 2 were obtained (equation 1), and acetylenic sulfonamides 3 were also converted to pyrrolidines 4 under the same reaction conditions (equation 2). It was expected that 6-membered products could be formed by the cyclization of N-5-alkenyl- or 5-alkynyl-N-benzoyloxysulfonamides 5 which has one more tether than the above substrate 1. However, instead of 6-membered piperidines, 5-membered pyrrolidines 6 were obtained as the major products. Abstraction of allylic or propargylic hydrogens by sulfonamidyl radicals was more favorable than the addition to the double or triple bonds (equation 3). Moreover, functionalization of unreactive C-H bonds of N-alkylsulfonamides 7 was achieved via 1,5-hydrogen abstraction to provide pyrrolidine derivatives. For example, spiro compound 8 was prepared in a good yield (equation 4). Thus, (CuOTf)2•C6H6-catalyzed cyclization of N-alkenyl, alkynyl and alkyl N- benzoyloxysulfonamides afforded efficient methods to prepare pyrrolidine derivatives via the sulfonamidyl radical formation. Remote functionalizations of unreactive C-H were also achieved in a catalytic manner.